Pelatihan Cara Deteksi Dini Gigi Berlubang, Gigi Berjejal, dan Kelainan dalam Mulut pada Komunitas Orang Tua dan Guru Playgoup dan TK Al-Alaq di Jatibening - Gadih Pratomo, Harris; Prijanti Dwisaptarini, Ade; Subrata, Aryadi; Nova Fitri , Andrian (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
The first 5 years of a child's development stage is a golden period in a child's growth and development period. Children's dental and oral health is very important, because the mouth is the first gate in the human digestive system. Parents' knowledge regarding dental and oral hygiene and health is the basis for forming children's behavior in maintaining children's oral and dental hygiene. Parents need to be provided with adequate knowledge on how to do an early detection of cavities, crowding of teeth, and abnormalities in the mouth as a form of prevention against tooth decay in children in the home environment. Community Service (PkM) was carried out online via Zoom Meeting on Friday 1 July 2022, and was attended by 37 people including teachers, staff and parents of students from Playgoup School and Kindergarten Al-Alaq Jatibening. The material provided is in the form of early detection of tooth decay, how to check oral health at home, how to detect crowding of teeth early, soft tissue disorders in the form of ppt, e-flyer and video. Measure success by completing a pre-test and post-test consisting of 17 knowledge questions related to the topic presented. It was found that participants' knowledge increased by 31%. The results obtained from this activity are very good with partners who are willing to carry out PkM activities on an ongoing basis.